If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 2(x + 10) = 5(x + -4) Reorder the terms: 3x + 2(10 + x) = 5(x + -4) 3x + (10 * 2 + x * 2) = 5(x + -4) 3x + (20 + 2x) = 5(x + -4) Reorder the terms: 20 + 3x + 2x = 5(x + -4) Combine like terms: 3x + 2x = 5x 20 + 5x = 5(x + -4) Reorder the terms: 20 + 5x = 5(-4 + x) 20 + 5x = (-4 * 5 + x * 5) 20 + 5x = (-20 + 5x) Add '-5x' to each side of the equation. 20 + 5x + -5x = -20 + 5x + -5x Combine like terms: 5x + -5x = 0 20 + 0 = -20 + 5x + -5x 20 = -20 + 5x + -5x Combine like terms: 5x + -5x = 0 20 = -20 + 0 20 = -20 Solving 20 = -20 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 650=x-(.028*x) | | 2x-7+6x=11+2x | | 6(q+2)=48 | | 2s+-111=9 | | 1a+3.1=6.6-4a | | 7+k=5k-40 | | 0=3x+3x | | 11t+13=7t+4 | | -9q=(-9)-8q | | 11*a-38=34 | | -15z-1=5-16z | | 5a/12+9a/11= | | 650=x-(2.8*x) | | 25+11=47 | | 1n-20=(-3n) | | 2q^2+3q-14=0 | | 8y-5=-1y+2 | | -4x-3(x-2)=20 | | 3x-5x+7=11x-19 | | -2h+10+1h=1h-10 | | 6c-8+3c=5c+12 | | -2*1/6= | | x/10-5=11/20 | | 12c-3c-19=11c+17 | | -13m=-37 | | 0.08-0.02(x+3)=-0.04(1-x) | | 4n^2-11n-78=0 | | 3.14x^2-128x^2= | | 3(4x-16)=2(4x+2) | | c*20= | | 3a+(a+5)=45 | | -49x^2+36=0 |